EVALUATION OF MOBILE DEVICE INDOOR MAPS FOR ORIENTATION TASKS - Sarot, Rhaíssa Viana; Delazari, Luciene Stamato (Boletim de Ciências Geodésicas, 2018)
This research investigates subjective user preference for using Floor Plans and Schematic Maps in an indoor environment, and how users locate and orient themselves when using these representations. We sought to verify the efficiency of these two kinds of digital maps and evaluate which elements found in physical environments and which elements found in the representations influence the user spatial orientation process. Users answered questions and performed orientation tasks which indicated their level of familiarity with the area being studied, their understanding of the symbology used, and their identification of Points of Interest (POI) in the environment. The initial results indicated a preference for the Schematic Map, because users thought that the symbology used on the map adopted was easy to understand.